On the superstability of the generalized orthogonality equation in Euclidean spaces - Chmieliński, Jacek (Annales Mathematicae Silesianae, 1994)
We consider a class of approximate solutions of the generalized orthogonality equation in ℝn (n≥2). We prove that this class coincides with the class of solutions of the equation, i.e., the superstability of the generalized orthogonality equation holds.